Bio-synthesis and characterization of nanoscaled CdO using corn husk extract via green nano-chemistry. (2021) - Bakayoko, M.; Sackey, J.; Razanamahandry, L.C.; Ngom, B.D.; Ntwampe, S.K.O.
Abstract: Cadmium oxide (CdO) nanoparticles were synthesized for the first time via an eco-friendly, simple and cost effective green synthesis method mediated by corn husk extract. Indeed, the corn husk extract acted as an effective chelating agent in facilitating the formation of the CdO nanoparticles. XRD analysis confirmed the formation of highly crystalline face-centred cubic CdO nanoparticles. The structural morphology and the constituents of the resultant CdO nanoparticles were investigated by High Resolution – Scanning Electron Microscopy (HR-SEM) and Energy Dispersive X- rays Spectroscopy (EDS). Attenuated Total Reflection – Fourier Transformer Infrared spectroscopy (ATR-FTIR) and Raman spectroscopy measurements have been obtained to complete the structural investigation. UV – Visible spectroscopy analysis showed a wide absorbance spectral range of 250 – 2500 nm. Consequently, the CdO nanoparticle displayed photoluminescence emission peak at 508 nm.